Population an introduction to concepts and issues - Weeks, John R (Boston Wadsworth)
Population introduces the basic concepts of population studies and helps to develop own demographic perspective, enabling to understand some of the most important issues confronting the world. The book sharpen the perception of population growth and chang
Keywords: Population